HUBUNGAN ANTARA MOTIVASI AKADEMIK DENGAN SELF-REGULATED LEARNING PADA MAHASISWA PASCA PANDEMI - Yogaswara, Almas Mushad; Hastuti, Rahmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Learning in the world of college is of course different from learning in schools, this can be seen from how teachers in lectures encourage their students to do self-regulated learning (SRL). Every student must have SRL, because the teaching given by the teacher in college is more focused on how the student is deeper into the material than what is given by the teacher. The purpose of this research is to find out whether there is a relationship between academic motivation and self-regulated learning in post- pandemic students. This study uses a quantitative non-probability-based sampling method and data collection is done online. This study had 151 participants aged 18-23. Academic motivation is measured by the Academic Motivation Scale (AMS) adapted by Vallerand et al. (1992), this measuring tool was later adapted by Natalya (2018) to become the Academic Motivational Scale - Indonesia Version. Self-regulated learning is measured by the Motivated Strategies for Learning Questionnaire (MSLQ) tool created by Pintrich and De Groot (1990). Based on the research results, this study showed that there was a relationship between the academic motivation variable and the SRL variable which obtained a value of (p=0.00; p<0.05) and a value of r = 0.716. This means that if an individual has high academic motivation, then that individual will also have a high SRL.